A Literature review on cooperative learning effects on student achievement in chemistry education - Edward Ifan Rumbewas; Achmad Rante Suparman; Faisal Faisal; Apriani Sulu Parubak (Arfak Chem: Chemistry Education Journal, 2026)
This study aims to evaluate the impact of implementing cooperative learning models on students' academic achievement in chemistry. The main focus of this research is to examine the effectiveness of various cooperative learning approaches such as Jigsaw, Student Teams Achievement Division (STAD), Think-Pair-Share (TPS), and Group Investigation in enhancing students' understanding of chemical concepts at the secondary school level. The method employed in this study is a literature review, drawing on previous research findings published in both national and international scientific journals. The analysis reveals that, in general, cooperative learning models positively contribute to improving students' performance in chemistry, particularly in terms of cognitive achievement, active participation, and conceptual understanding. However, some research gaps were also identified, including the limited number of studies using mixed-methods approaches, the lack of exploration at the 11th and 12th grade levels, minimal integration with TPACK-based digital technology, and the suboptimal analysis of individual student factors such as gender and learning styles. These findings highlight the need for more comprehensive, context-specific follow-up research on the implementation of cooperative models in chemistry education